Climate-smart financial diaries for scaling in Nyando Basin: Factsheet midterm findings Global Challenges Programme Call 4 - Food & Business Knowledge Platform; NWO-WOTRO Science for Global Development; CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate change requires a change in the way people produce food, since changing rain seasons and more frequent droughts and floods destroy harvests. Possible solutions include new seeds and improved crop management, new animal breeds that can thrive in the changing climatic conditions and water management. In the Nyando Basin in West Kenya farmers suffer from climate change and hence adapting one or more of these measures is needed. However, an important question is whether it is possible for all farmers to take this step. Do they have enough resources to finance these investments? Where could they borrow the required money? This GCP-4 project aims to find out if farmers in Nyando Basin – male and female – have access to credit in ways that can be upscaled to other farmers in the region and elsewhere, and how this takes shape. For this purpose the project consortium has been interviewing all financially active persons in 123 households in the area for 29 weeks now, with 21 weeks to go, focusing on their financial activities. Also the project will assess the impact of large-scale adoption of new technologies for the environment and the local economy. Finally, the project group has started to engage buyers of produce and providers of inputs as potential sources of credit to support Climate Smart Agricultural practices.